Effects of Caffeine on Splanchnic Oxygenation in Preterm Infants - Ilhan, Ozkan; Bor, Meltem (American Journal of Perinatology, 2020)
Objective The aim of this study is to assess the effects of administering 20 mg/kg loading dose of caffeine citrate intravenously on splanchnic oxygenation in preterm infants.Study Design The infants with a gestational age (GA) of <34 weeks who were administered with a 20 mg/kg intravenous loading dose of caffeine citrate within 48 hours after birth were investigated prospectively. Regional splanchnic oxygen saturation (rsSO2) and splanchnic fractional tissue oxygen extraction rate (sFTOE) were measured using near-infrared spectroscopy before caffeine infusion, immediately after caffeine infusion and 1, 2, 3, 4, and 6 hours (h) after dose completion; postdose values were compared with predose values.Results A total of 41 infants with a mean GA of 29.2 ± 1.6 weeks and birth weight of 1,315 ± 257 g as well as postnatal age of 32.2 ± 10.8 hours were included in the study. rsSO2 significantly reduced from 63.1 to 57.5% immediately after caffeine infusion, 55.1% after 1 hour, and 55.2% after 2 hours with partial recovery at 3-hour postdose. sFTOE increased correspondingly.Conclusion Caffeine reduces splanchnic oxygenation and increases splanchnic oxygen extraction for at least 2 hours with partial recovery to predose levels at 3-hour postdose.
Keywords: caffeine; near infrared spectroscopy; preterm infant; regional tissue oxygenation; splanchnic oxygenation